Effect of Sonication on The Mechanical Properties of Organic Mixed Grain Bread (Agricultural Engineering, 2018)
The aim of this study was to determine the effect of ultrasound waves on mechanical properties of organic bread. Mixed grain bread baked at a local bakery according to its original recipe was the material subjected to testing. Prior to baking, the dough was sonicated at frequencies of 20 kHz and 40 kHz for 3 minutes, and at a frequency of 100 kHz for 3 minutes and 6 minutes. The mechanical properties of the bread (compression test, penetration test and TPA) were examined after 24 h, 48 h and 72 h following the baking process. The maximum work obtained in the compression test after 24 h following the baking ranged from 616 N to 668 N. On the next day following the baking, the maximum work value ranged from 750 N to 898 N, while after 72 hours, it ranged from 988 N to 1135 N. In the penetration test, the following results were obtained: after 24 hours, the force value ranged from 2.71 N to 3.17 N; after 48 hours following the baking, it ranged from 4.90 N to 6.35 N; and after 72 hours following the baking, from 3.98 N to 6.88 N. As regards elasticity, the obtained results fell within the following ranges: after 24 hours following the baking, from 0.53 to 0.58; after 48 hours following the baking, from 0.43 to 0.55; and after 72 hours following the baking, from 0.40 to 0.45. Gumminess measured after 24 hours following the baking ranged from 8.75 N to 18.71 N; after 48 hours, from 10.83 N to 15.48 N; and after 72 hours, the gumminess values ranged from 15.57 N to 19.06 N. As regards chewiness, the following results were obtained: after 24 hours following the baking, from 8.00 N to 17.59 N; after 48 hours following the baking, from 9.77 N to 13.87 N; and after 72 hours following the baking, from 12.56 N to 16.85 N. The frequencies and durations of sonication applied changed no mechanical properties of the tested bread.